Perlindungan Hukum terhadap Konsumen dalam Transaksi Jual Beli melalui E-Commerce di Indonesia: Studi Putusan 629/Pdt.G/2020/Pn Jkt.Sel - Farida Rosadi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The advancement of information technology has led to a rise in e-commerce purchases and sales, facilitating convenience for the public, but also giving rise to legal concerns regarding consumer protection. This study focuses on examining the legal framework for consumer protection and the legal certainty of compensation mechanisms in e-commerce transactions. The method applied is doctrinal legal research accompanied by a statutory and conceptual approach. The findings indicate that consumer protection has been accommodated in the Consumer Protection Act and the Electronic Information and Transactions Act, but the regulation of compensation mechanisms remains incomplete, creating legal uncertainty. Therefore, harmonization and regulatory reform are needed to strengthen consumer protection in e-commerce transactions.